Development and differentiation of midbrain dopaminergic neuron: from bench to bedside - Wang, Mengmeng; Ling, King-Hwa; Tan, Jun Jie; Lu, Cheng-Biao (Multidisciplinary Digital Publishing Institute, 2020)
Parkinson’s Disease (PD) is a neurodegenerative disorder affecting the motor system. It is primarily due to substantial loss of midbrain dopamine (mDA) neurons in the substantia nigra pars compacta and to decreased innervation to the striatum. Although existing drug therapy available can relieve the symptoms in early-stage PD patients, it cannot reverse the pathogenic progression of PD. Thus, regenerating functional mDA neurons in PD patients may be a cure to the disease. The proof-of-principle clinical trials showed that human fetal graft-derived mDA neurons could restore the release of dopamine neurotransmitters, could reinnervate the striatum, and could alleviate clinical symptoms in PD patients. The invention of human-induced pluripotent stem cells (hiPSCs), autologous source of neural progenitors with less ethical consideration, and risk of graft rejection can now be generated in vitro. This advancement also prompts extensive research to decipher important developmental signaling in differentiation, which is key to successful in vitro production of functional mDA neurons and the enabler of mass manufacturing of the cells required for clinical applications. In this review, we summarize the biology and signaling involved in the development of mDA neurons and the current progress and methodology in driving efficient mDA neuron differentiation from pluripotent stem cells.